2011
DOI: 10.1504/gber.2011.040728
|View full text |Cite
|
Sign up to set email alerts
|

The value relevance of losses revisited: the importance of earnings aggregation

Abstract: Prior research has suggested that earnings explain a larger portion of the variation in stock returns when disaggregated into components. This study shows that the increase in explanatory power stems primarily from disaggregation of negative earnings. When accounting earnings are sufficiently disaggregated into items, there is no longer a statistical difference in the value relevance of positive and negative earnings. Thus, negative earnings are also useful to stock investors. The findings are attributed to ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
2
1
Order By: Relevance
“…Ahmadi (2017) also found that value relevance declined when firms had negative earnings. Contrary to these researchers' findings, Beisland (2011) found that disaggregated negative earnings are equally value relevant, arguing that losses provide information relevant to firm valuation. Lack of persistence of negative earnings is cited in literature as the main reason why losses are deemed not value relevant (Barth et al, 2005;Carnes, 2006).…”
Section: Discussion Of Findingscontrasting
confidence: 91%
See 3 more Smart Citations
“…Ahmadi (2017) also found that value relevance declined when firms had negative earnings. Contrary to these researchers' findings, Beisland (2011) found that disaggregated negative earnings are equally value relevant, arguing that losses provide information relevant to firm valuation. Lack of persistence of negative earnings is cited in literature as the main reason why losses are deemed not value relevant (Barth et al, 2005;Carnes, 2006).…”
Section: Discussion Of Findingscontrasting
confidence: 91%
“…In the dummy variables regression models, the dummy variable is significant at 1% level and all robustness checks show that the models are quite robust. The findings both confirm and contradict what other scholars found out: they are contrary to scholars like Kwon (2017) and Venter et al (2014) but are consistent with Beisland (2011) and Jahmani et al (2017). This research rejects the hypothesis that the market punishes loss firms, resulting in lack of value relevance of negative earnings.…”
Section: Discussion Of Findingssupporting
confidence: 58%
See 2 more Smart Citations